Faktor Risiko Kejadian Difteri di Jawa Timur: Status Gizi Kurang dan Cakupan Imunisasi DPT-HB-HiB3 (Tahun 2019-2021) - Shafa Ainunnissa Suratno; Lucia Yovita Hendrati (Media Gizi Kesmas, 2023)
Background: One of the efforts to tackle diphtheria is by giving DPT-HB-HiB3 immunization and improving nutritional status, especially in increasing toddler weight. East Java Province has experienced a decrease in DPT-HB-HiB3 immunization coverage in 2020 and 2021 and has experienced an increase in the amount of underweight status in 2020. Objectives: The purpose of this study is to describe the relationship between diphtheria incidence and underweight status and DPT-HB-HiB3 immunization coverage in 38 districts/cities in East Java Province in 2019-2021. Methods: The method in this study used a population correlation study design to analyze secondary data from the 2019-2021 East Java Province Health Profile Book, which was processed using the Health Mapper and SPSS applications. Results: In 2019, there was a relationship between underweight status and the incidence of diphtheria (0.479) and there was a relationship between DPT-HB-HiB3 immunization coverage and the incidence of diphtheria (0.531). In 2020, there is no relationship between underweight status and the incidence of diphtheria (0.065) and there is no relationship between DPT-HB-HiB3 immunization coverage and the incidence of diphtheria (0.275). In 2021, there is no relationship between underweight status and the incidence of diphtheria (0.050) and there is no relationship between DPT-HB-HiB3 immunization coverage and the incidence of diphtheria (0.258). Conclusions: The coverage of DPT-HB-HiB3 immunization and the amount of underweight status were both associated with diphtheria incidence in 2019, while the coverage of DPT-HB-HiB3 immunization and the amount of underweight status were both not associated with the incidence of diphtheria in 2020 and 2021.